Subretinal gnathostomiasis: A successful focal laser photocoagulation for a living parasite - Supalert Prakhunhungsit (2022)
Purpose: To report a case of subretinal gnathostomiasis presenting with progressive subretinal tracts of a living parasite and successfully treated with focal laser photocoagulation. Method: Observational case report. Patient: A 29-year-old Thai male complained of blurred vision and floaters in his left eye for two weeks. An ocular examination showed multiple, whitish, subretinal tracks at the superotemporal retina. After 5 days of oral albendazole, a moving parasite was confirmed by multimodal retinal imaging. An immunoblotting analysis was positive for Gnathostoma species. Result: The patient was treated by laser photocoagulation with frequency-doubled Nd:YAG laser around and over the parasite. Oral albendozole was continued and naproxen was prescribed for four weeks. His vision improved to 20/20 and the inflammation subsided completely within three months. The patient has been followed for five years without local and systemic complications. Conclusions: Focal laser photocoagulation without systemic steroids could be a successful treatment for active subretinal gnathostomiasis with a satisfactory safety profile in a long-term follow-up.